Przemiany w strukturze funkcjonalnej Jeleniej Góry w latach 1999-2002 - Przybyła, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article concerns the identification of dominative functions of Jelenia Góra and functions in which the town has been specialized. The research has been conducted on the basis of size, structure and changes of employment. The theory of economic base of town has been used to specify the town-build functions of Jelenia Góra. The base has been measured by two methods - indicator of surplus of employees and Florence's coefficient of specialization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 414-421